Synthesis Of CMC Pectin Hydrogel (1:2) Using the Freeze-Thaw Method and Its Benefit as An Adsorbent - Andini, Sri; Maelan, Nabilla Maharani; Dewi, Nurazizah Melani; Perdani, Meka Saima; Wahyuningtyas, Aulia (Journal of The Indonesian Society of Integrated Chemistry, 2024)
Research has been conducted on the manufacture of hydrogels from CMC and Pectin (1:2), which can be applied as an adsorbent. The Citarum River is included in the category of the most polluted river in the world, because it contains chemicals that can reduce water quality. One of the pollutants is the Cu2+ metal, precisely at the entrance point of the Citarum river which exceeds the threshold. Cu2+ metal is not biodegradable and can accumulate in the human body, which causes severe health problemss. Metal Cu2+ can cause toxic effects on fish body tissues that can induce the production of Reactive Oxygen Species (ROS). CMC and pectin are organic materials that are used as hydrogels to absorb Cu2+ metal. Hydrogel CMC/Pectin is analyzed using FTIR by having groups O-H, C=O, C-H, OH bending, COOH streatching vibration and C-O-C. The result from BET is that the hydrogel has a surface area of 3.706 m²/g and is classified as a type 1 isotherm graph, and has small pores. The optimum condition of the adsorption process occurs at a concentration of 260 ppm, using the Langmuir isotherm model and has an adsorption capacity of 19.76 mg/g with an absorption efficiency of 68.60%.).